Gillian Armstrong Popular, Sensual & Ethical Cinema - Erhart, Julia (Edinburgh University Press, 2020)
A commercially successful Australian director of over eighteen feature films and documentaries, including My Brilliant Career (1979), Gillian Armstrong is an early, notable example of a woman director connecting with mass audiences. Armstrong's films are unique in their aesthetic expression and in the ethical relationships that they depict, framed through the language of gender inclusivity and due in part to her foregrounding of original, complex and nuanced female characters. This important book fills a gap in the literature on women screen practitioners and is a long overdue response to demands for new insight into the work of this significant director.